Dynamic traction of lattice-confined platinum atoms into mesoporous carbon matrix for hydrogen evolution reaction - Lou, David Xiong Wen (2018)
Constructing atomically dispersed platinum (Pt) electrocatalysts is essential to build high-performance and cost-effective electrochemical water-splitting systems. We present a novel strategy to realize the traction and stabilization of isolated Pt atoms in the nitrogen-containing porous carbon matrix (Pt@PCM). In comparison with the commercial Pt/C catalyst (20 weight %), the as-prepared Pt@PCM catalyst exhibits significantly boosted mass activity (up to 25 times) for hydrogen evolution reaction. Results of extended x-ray absorption fine structure investigation and density functional theory calculation suggest that the active sites are associated with the lattice-confined Pt centers and the activated carbon (C)/nitrogen (N) atoms at the adjacency of the isolated Pt centers. This strategy may provide insights into constructing highly efficient single-atom catalysts for different energy-related applications.